Das sogenannte ,Königliche Gerichtsbuch' - Aufzeichnungen des Michael von Pfullendorf zu den Anfängen des Kammergerichts am römisch-deutschen Königshof (1442 bis 1451) Einführung und Edition - Luger, Daniel (2022)
This publication offers an edition of the "Royal court book" in full text. It starts with a foreword by Bernhard Diestelkamp, who underlines the central importance of this source for research. In the extensive analysis that follows, the applicant classifies the book into legal and cultural-historical research.